Enhancement of Postura MotergoTM: From an Ergonomic Motorcycle Test Rig to a Full-Scale Simulator / Wan Muhammad Syahmi Wan Fauzi ...[et al.] - Wan Fauzi, Wan Muhammad Syahmi; Omar, Abdul Rahman; Rashid, Helmi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Motorcycle road accidents have become a global transportation issue. In enabling scientific studies on indoor motorcycling, Postura MotergoTM motorcycle test rig was initially established by a group of researcher from the Motorcycle Engineering Technology Laboratory (METAL). Unique from other test rigs, the patented Postura MotergoTM was designed to be fully adjustable in order to replicate different type of riding postures. However, it is noticeable that the current design of Postura MotergoTM could be improved to further elevate users’ experience into a full-scale simulator. The aim of this study was to enhance the features of Postura MotergoTM’s test rig, adding to better fidelity and ensuring the design longevity and overall cost effectiveness provided by the newly enhanced motorcycle simulator. In improving the Postura MotergoTM, it can be divided into 2 categories: (i) Design Aspect Category (DAC), and (ii) Environmental Simulator Category (ESC). The DAC covers parts of Postura MotergoTM’s test rig which is the main chassis, handlebars, foot-pegs, tank cover and the platform or base of the simulator. The ESC involves the enhancement of Human-Machine-Environment Interface (HMEI) elements. As of the methodology, state-of-the-art CATIA V5R20 software was extensively used in redesigning the Postura MotergoTM whilst the fabrication works were done in-house at the Machine Workshop, Faculty of Mechanical Engineering, Universiti Teknologi MARA, Shah Alam, Malaysia. As a whole, these categories ensured the complete construction of an immersive motorcycle simulator. Conclusively, by enhancing the Postura MotergoTM test rig, greater near-to-real motorcycling conditions could be simulated in a controlled laboratory setting and narrowing the fidelity and validity values. Thus, it enables the particular motorcycle simulator to contribute to various motorcycle ergonomics researches in the near future. Such matter would then be hoped to ultimately aid in reducing the global motorcycle road accident statistics.